ประวัติศาสตร์สามัญชนในสังคมไทยสมัยแรกเริ่มรัฐประชาชาติ พ.ศ. 2475-2490 - ศราวุฒิ วิสาพรม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This thesis aims to study the effects of the revolution in 1932 onThai society, especially on the life of commoners during 1932-1947. This research begins by considering the revolution as the transformation of the Thai state - from absolutist state to beginning of nation state - which spurred great changes in political, economic and cultural realms. The transformation of the political structure had offered the opportunity for commoners to enter “the political space” for the first time via modern political institutions. Furthermore, the revolution had also rapidly increased the number of commoners in the modernized bureaucracy. As for the socio-economic changes, in the 1930s and 1940s, there was a positive sign of change in which commoners gained more access to justice, reflected in the promulgation of many laws in their favor, including the significant changes in the Revenue Code. Moreover, the Second World War had enhanced not only the opportunity for commerce in rural areas but also and the increased capital accumulation of the Thai-Chinese merchants due to the widespread of the “illegal economy”, as well as the Japanese army’s demand for various kinds of products. The great cultural transformation during the early nation state period includes the changing role of the state towards providing more “service” to the people, but the same time also to “control” them via various social institutions, such as schools, media, public health agencies, etc. Most people reacted to these actions and they learned and continued to reproduce the state ideology, a phenomenon which could be seen both in the central area and in other provinces. Nevertheless, some went against the state. With these reasons, the political activities of commoners continued in a lively fashion. In addition, the social relations became more equal and modern, even though many rights, freedom and equality were still limited by the political context at that time. Unlike “liberal democracy”, the state during the World War II era still exercised power as a dictator regime. In summary, this thesis argues that the Thai society and commoners’ life in the wake of the 1932 revolution has undergone far more transformations than the previous studies on the period allow.